Carbon nanotube antistatic protective film and preparation method thereof
Through the combination of CM@CNTs-PDA antistatic agent and low viscosity silicone rubber, the interaction between polydopamine coating and nanocellulose is used to solve the dispersion of carbon nanotubes in silicone rubber, and low foreign matter and high performance are prepared. The carbon nanotube antistatic protective film meets the use requirements of high-end products.
Patent Information
- Application Number
- CN202411168055.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-13
AI Technical Summary
The existing carbon nanotube antistatic agents have many foreign matters such as carbon dots and rubber dots after film formation in silicone rubber, which cannot meet the quality requirements of high-end products.
Using CM@CNTs-PDA antistatic agent, polydopamine coating was carried out by reacting dopamine precursor solution with carbon nanotubes, combining the non-covalent interaction of nanocellulose, CM@CNTs-PDA antistatic agent was prepared, and Doped with low viscosity silicone rubber, a carbon nanotube antistatic protective film is formed by grinding.
It significantly reduces foreign matter such as carbon dots and glue dots, achieves permanent antistatic properties and high temperature stability, has low surface resistivity, and meets the use requirements of high-end products.
Smart Images

Figure CN119119732A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicone rubber antistatic protective films, and in particular relates to a carbon nanotube antistatic protective film and a preparation method thereof. Background Art
[0002] During the production and transportation of electronic products, protective films are required to protect the corresponding parts, support the bottom, and discharge waste. Silicone (silicone rubber) protective films are increasingly used in the electronics industry due to their excellent adhesion and stable bonding properties. However, due to their inherent properties, the application of silicone protective films in some areas is also limited: for example, products with high requirements for antistatic properties, because silicone is a polymer material with good insulation properties, and the resistivity of ordinary silicone rubber protective film products is generally 10 12 -10 15 Ω, static electricity will accumulate during use, resulting in a higher tearing voltage, which may break down electronic components in severe cases, causing defects and increasing the company's production costs.
[0003] In order to eliminate static electricity, antistatic agents are added to silicone rubber to produce antistatic silicone rubber. Antistatic silicone rubber means that the static electricity phenomenon caused by friction and accumulation of charges on the surface of silicone rubber due to its excellent insulation properties is suppressed or eliminated, so that the surface of silicone rubber products remains clean and no longer absorbs small particles such as dust or releases static electricity. Permanent antistatic means that the antistatic performance of the material will not be greatly affected by environmental factors and time.
[0004] Common antistatic agents for silicone rubber mainly include ionic antistatic agents, polymer antistatic agents, conductive carbon black, carbon fiber, etc., which achieve antistatic properties by reducing the resistivity of silicone rubber. Among them, carbon nanotube (CNT) antistatic agents have the characteristics of small addition amount, permanent conductivity, small impact on the impact strength of materials, and no decarbonization of materials compared with other antistatic agents. They will be widely used in the electronics field as a new type of conductive additive. However, the existing carbon nanotube antistatic agents will have many problems such as carbon dots, glue dots, and foreign matter after being added to the glue system to form a film. For high-end products with strict control over appearance, this type of carbon nanotube antistatic agent does not meet the quality of use. Summary of the invention
[0005] One of the purposes of the present invention is to provide a carbon nanotube antistatic protective film to solve the problem of a large number of foreign matters such as carbon dots and glue dots in the organic silicon antistatic protective film in the prior art.
[0006] A second object of the present invention is to provide a method for preparing a carbon nanotube antistatic protective film.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] In a first aspect, a carbon nanotube antistatic protective film comprises the following components in parts by weight:
[0009] CM@CNTs-PDA antistatic agent 1-3 parts;
[0010] Silicone rubber 95-98 parts;
[0011] 1-2 parts of cross-linking agent;
[0012] The CM@CNTs-PDA antistatic agent is prepared by the following steps:
[0013] S1. Add dopamine precursor solution to carbon nanotube (CNTs) suspension, stir and react for 10-24h, collect by centrifugation and vacuum dry to obtain product 1;
[0014] S2. The product 1 is placed in a N2 atmosphere, and after gradient calcination, it is naturally cooled to room temperature (25-30°C) to obtain polydopamine (PDA) in situ polymerization-coated CNTs (CNTs-PDA);
[0015] S3. Add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), hydroxysuccinimide (NHS) and CNTs-PDA to the nanocellulose (CM) solution, mix well, adjust the pH to 4-6, stir and react under vacuum conditions for 8-20 hours. After the reaction is completed, collect by centrifugation and vacuum dry to obtain CM@CNTs-PDA antistatic agent.
[0016] As a further solution of the present invention, the mass percentage of CNTs and dopamine precursor in S1 is 55-65:35-45wt%.
[0017] As a further solution of the present invention, the N2 flow rate in S2 is 10-20 mL / min.
[0018] As a further solution of the present invention, the gradient calcination in S2 is specifically to heat the temperature to 200-250°C at a heating rate of 3-5°C / min, keep it warm for 0.5-1.5h, then heat the temperature to 320-350°C at a heating rate of 1-2°C / min, and keep it warm for 0.5-1.5h.
[0019] As a further solution of the present invention, the mass concentration of the nanocellulose (CM) solution in S3 is 0.4-0.8wt%.
[0020] As a further embodiment of the present invention, the usage ratio of the nanocellulose solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, hydroxysuccinimide and CNTs-PDA in S3 is 100 mL: 0.5-0.6 g: 0.2-0.4 g: 0.6-0.9 g.
[0021] As a further solution of the present invention, the stirring speed is 100-300 rpm.
[0022] In a second aspect, a method for preparing a carbon nanotube antistatic protective film comprises the following steps:
[0023] Step 1, adding 1-3 parts of CM@CNTs-PDA antistatic agent and 1-2 parts of crosslinking agent to 95-98 parts of silicone rubber, stirring and mixing to obtain carbon nanotube antistatic silicone rubber material;
[0024] Step 2: Add the carbon nanotube antistatic silicone rubber material into a grinder, grind it for 9-12 times under the condition of a roller pressure of 4.5-5.5 kg, and then cure the coating at room temperature to obtain a carbon nanotube antistatic protective film.
[0025] As a further solution of the present invention, the stirring speed in step 1 is 200-400 rpm.
[0026] As a further solution of the present invention, the viscosity of the silicone rubber is 500-1500 mPa·s, and it is a commercially available conventional low-viscosity silicone rubber, such as 107 silicone rubber.
[0027] As a further embodiment of the present invention, the cross-linking agent is a conventional commercially available cross-linking agent, such as Dow SYL-OFFTM SL7028.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention provides a carbon nanotube antistatic protective film and a preparation method thereof. CM@CNTs-PDA is used as an antistatic agent and doped with low-viscosity silicone rubber. By improving the dispersibility of carbon nanotubes in the silicone rubber system, the prepared silicone-based protective film has fewer carbon dots, glue dots, and foreign matter, has permanent antistatic properties, good stability, excellent high temperature resistance, and low surface resistivity, which effectively meets the use requirements.
[0030] 2. In the present invention, carbon nanotubes are used as antistatic fillers in the silicone rubber system. Due to their large surface energy, they are easy to agglomerate, and the tubes are easy to entangle with each other, resulting in a large number of foreign matter such as carbon dots and glue dots after film formation. First, by using polydopamine to in-situ coat them, the amorphous polydopamine provides more active sites for the carbon nanotubes, further enhancing their conductive properties, and the carbon nanotubes further provide a conductive framework for polydopamine, thereby improving the mechanical properties of the material. Secondly, through the non-covalent interaction between the functional groups such as phenolic hydroxyl and amino groups in polydopamine and the hydroxyl groups in the nanocellulose molecules, the nanocellulose is grafted onto the polydopamine-coated carbon nanotubes, and polydopamine is used as an intermediate medium for bidirectional hydroxyl functionalization, thereby giving the modified carbon nanotubes good dispersibility and flexibility in the silicone rubber system. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described below in conjunction with the accompanying drawings.
[0032] Figure 1 It is a schematic diagram of the preparation process of a carbon nanotube antistatic protective film of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Please refer to Figure 1 ; CM@CNTs-PDA antistatic agent, prepared by the following steps:
[0035] S1. Add a dopamine precursor solution to a CNTs suspension having a mass concentration of 0.4-0.8wt%, wherein the mass percentage of CNTs and dopamine precursor is 55-65:35-45wt%, and react at 100-300rpm for 10-24h, collect by centrifugation, and dry in vacuum to obtain product 1;
[0036] S2. The product 1 was placed in a N2 atmosphere with a flow rate of 10-20 mL / min, heated to 200-250°C at a heating rate of 3-5°C / min, kept warm for 0.5-1.5 h, and then heated to 320-350°C at a heating rate of 1-2°C / min, kept warm for 0.5-1.5 h for gradient calcination, and then naturally cooled to room temperature to obtain CNTs-PDA;
[0037] S3. According to the dosage ratio of nanocellulose solution, EDC, hydroxy-NHS and CNTs-PDA of 100mL: 0.5-0.6g: 0.2-0.4g: 0.6-0.9g, EDC, NHS and CNTs-PDA were added to the nanocellulose solution with a mass concentration of 0.4-0.8wt%, mixed evenly, adjusted the pH to 4-6, and stirred at 100-300rpm under vacuum conditions for 8-20h. After the reaction, centrifugation was collected and vacuum dried at 40-80℃ to obtain CM@CNTs-PDA antistatic agent.
[0038] A method for preparing a carbon nanotube antistatic protective film comprises the following steps:
[0039] Step 1, adding 1-3 parts of CM@CNTs-PDA antistatic agent and 1-2 parts of crosslinking agent to 95-98 parts of silicone rubber with a viscosity of 500-1500 mPa·s, stirring and mixing at a speed of 200-400 rpm to obtain a carbon nanotube antistatic silicone rubber material;
[0040] Step 2: Add the carbon nanotube antistatic silicone rubber material into a grinder, grind it for 9-12 times under the condition of a roller pressure of 4.5-5.5 kg, and then cure the coating at room temperature to obtain a carbon nanotube antistatic protective film.
[0041] The crosslinking agent in the following examples and comparative examples is Dow SYL-OFF™ SL 7028, which is commercially available.
[0042] Example 1
[0043] CM@CNTs-PDA antistatic agent was prepared by the following steps:
[0044] S1. Add a dopamine precursor solution to a CNTs suspension having a mass concentration of 0.6 wt%, wherein the mass percentage of CNTs to dopamine precursor is 60:40 wt%, and react at 200 rpm for 18 h, collect by centrifugation, and dry in vacuum to obtain product 1;
[0045] S2. The product 1 was placed in a N2 atmosphere with a flow rate of 15 mL / min, heated to 230°C at a heating rate of 4°C / min, kept at that temperature for 1 h, and then heated to 340°C at a heating rate of 1.5°C / min, kept at that temperature for 1 h for gradient calcination, and then naturally cooled to room temperature to obtain CNTs-PDA;
[0046] S3. According to the dosage ratio of nanocellulose solution, EDC, hydroxy-NHS and CNTs-PDA of 100mL: 0.55g: 0.3g: 0.8g, EDC, NHS and CNTs-PDA were added to the nanocellulose solution with a mass concentration of 0.6wt%, and mixed evenly. The pH was adjusted to 5 with dilute hydrochloric acid, and the reaction was stirred at 200rpm under vacuum conditions for 14h. After the reaction, the mixture was collected by centrifugation and dried in vacuum at 60°C to obtain CM@CNTs-PDA antistatic agent.
[0047] Example 2
[0048] CM@CNTs-PDA antistatic agent was prepared by the following steps:
[0049] S1. Add a dopamine precursor solution to a CNTs suspension having a mass concentration of 0.4 wt%, wherein the mass percentage of CNTs to dopamine precursor is 65:35 wt%, and react at 200 rpm for 18 h, collect by centrifugation, and vacuum dry to obtain product 1;
[0050] S2. The product 1 was placed in a N2 atmosphere with a flow rate of 15 mL / min, heated to 230°C at a heating rate of 4°C / min, kept at that temperature for 1 h, and then heated to 340°C at a heating rate of 1.5°C / min, kept at that temperature for 1 h for gradient calcination, and then naturally cooled to room temperature to obtain CNTs-PDA;
[0051] S3. According to the dosage ratio of nanocellulose solution, EDC, hydroxy-NHS and CNTs-PDA of 100mL: 0.5g: 0.4g: 0.6g, EDC, NHS and CNTs-PDA were added to the nanocellulose solution with a mass concentration of 0.8wt%, and mixed evenly. The pH was adjusted to 5 with dilute hydrochloric acid, and the reaction was stirred at 200rpm under vacuum conditions for 16h. After the reaction, the mixture was collected by centrifugation and dried in vacuum at 50°C to obtain CM@CNTs-PDA antistatic agent.
[0052] Example 3
[0053] CM@CNTs-PDA antistatic agent was prepared by the following steps:
[0054] S1. Add a dopamine precursor solution to a CNTs suspension having a mass concentration of 0.8 wt%, wherein the mass percentage of CNTs to dopamine precursor is 55:45 wt%, and react at 200 rpm for 20 h, collect by centrifugation, and vacuum dry to obtain product 1;
[0055] S2. The product 1 was placed in a N2 atmosphere with a flow rate of 15 mL / min, heated to 230°C at a heating rate of 4°C / min, kept at that temperature for 1 hour, and then heated to 320°C at a heating rate of 1.5°C / min, kept at that temperature for 1 hour for gradient calcination, and then naturally cooled to room temperature to obtain CNTs-PDA;
[0056] S3. According to the dosage ratio of nanocellulose solution, EDC, hydroxy-NHS and CNTs-PDA of 100mL: 0.6g: 0.2g: 0.9g, EDC, NHS and CNTs-PDA were added to the nanocellulose solution with a mass concentration of 0.4wt%, and mixed evenly. The pH was adjusted to 5 with dilute hydrochloric acid, and the reaction was stirred at 200rpm under vacuum conditions for 18h. After the reaction, the mixture was collected by centrifugation and dried in vacuum at 50°C to obtain CM@CNTs-PDA antistatic agent.
[0057] Example 4
[0058] A method for preparing a carbon nanotube antistatic protective film comprises the following steps:
[0059] Step 1, add 2 parts of CM@CNTs-PDA antistatic agent prepared in Example 1 and 1 part of crosslinking agent to 97 parts of 107 silicone rubber, and stir and mix at a speed of 300 rpm to obtain a carbon nanotube antistatic silicone rubber material;
[0060] Step 2: Add the carbon nanotube antistatic silicone rubber material into a grinder, grind it 10 times under the condition of a roller pressure of 5 kg, and then cure the coating at room temperature to obtain a carbon nanotube antistatic protective film.
[0061] Example 5
[0062] A method for preparing a carbon nanotube antistatic protective film, the preparation method is the same as that of Example 4, except that only the CM@CNTs-PDA antistatic agent prepared in Example 1 is replaced by the CM@CNTs-PDA antistatic agent prepared in Example 2, and the other components and parameters remain unchanged.
[0063] Example 6
[0064] A method for preparing a carbon nanotube antistatic protective film, the preparation method is the same as that of Example 4, except that only the CM@CNTs-PDA antistatic agent prepared in Example 1 is replaced by the CM@CNTs-PDA antistatic agent prepared in Example 3, and the other components and parameters remain unchanged.
[0065] Comparative Example 1
[0066] A method for preparing a carbon nanotube antistatic protective film comprises the following steps:
[0067] Step 1: Preparation of CNTs-PDA antistatic agent:
[0068] S1. Add a dopamine precursor solution to a CNTs suspension having a mass concentration of 0.6 wt%, wherein the mass percentage of CNTs to dopamine precursor is 60:40 wt%, and react at 200 rpm for 18 h, collect by centrifugation, and dry in vacuum to obtain product 1;
[0069] S2. The product 1 was placed in a N2 atmosphere with a flow rate of 15 mL / min, heated to 230°C at a heating rate of 4°C / min, kept at that temperature for 1 h, and then heated to 340°C at a heating rate of 1.5°C / min, kept at that temperature for 1 h for gradient calcination, and then naturally cooled to room temperature to obtain CNTs-PDA;
[0070] Step 2, adding 2 parts of CNTs-PDA antistatic agent and 1 part of crosslinking agent to 97 parts of 107 silicone rubber, stirring and mixing at a speed of 300 rpm to obtain a carbon nanotube antistatic silicone rubber material;
[0071] Step 3: Add the carbon nanotube antistatic silicone rubber material into a grinder, grind it 10 times under the condition of a roller pressure of 5 kg, and then cure the coating at room temperature to obtain a carbon nanotube antistatic protective film.
[0072] Comparative Example 2
[0073] A method for preparing a carbon nanotube antistatic protective film comprises the following steps:
[0074] Step 1: Preparation of CM@CNTs antistatic agent:
[0075] According to the dosage ratio of nanocellulose solution, EDC, NHS and CNTs of 100 mL: 0.5 g: 0.4 g: 0.6 g, EDC, NHS and CNTs were added to the nanocellulose solution with a mass concentration of 0.8 wt%, mixed evenly, the pH was adjusted to 5 with dilute hydrochloric acid, stirred at 200 rpm under vacuum conditions for 16 h, and after the reaction was completed, centrifuged and collected, and vacuum dried at 50 ° C to obtain CM@CNTs antistatic agent;
[0076] Step 2, add 2 parts of CM@CNTs antistatic agent and 1 part of crosslinking agent to 97 parts of 107 silicone rubber, stir and mix at a speed of 300 rpm to obtain carbon nanotube antistatic silicone rubber material;
[0077] Step 3: Add the carbon nanotube antistatic silicone rubber material into a grinder, grind it 10 times under the condition of a roller pressure of 5 kg, and then cure the coating at room temperature to obtain a carbon nanotube antistatic protective film.
[0078] Comparative Example 3
[0079] A method for preparing a carbon nanotube antistatic protective film, the preparation method is the same as that of Example 4, except that only the CM@CNTs-PDA antistatic agent prepared in Example 1 is replaced by CNTs, and the other components and parameters remain unchanged.
[0080] Comparative Example 4
[0081] A method for preparing a carbon nanotube antistatic protective film comprises the following steps:
[0082] Step 1, weighing CNTs, dopamine precursor and nanocellulose according to a mass ratio of 12:8:15, and mixing the obtained material evenly as an antistatic agent;
[0083] Step 2, adding 2 parts of the antistatic agent obtained in step 1 and 1 part of the cross-linking agent to 97 parts of 107 silicone rubber, stirring and mixing at a speed of 300 rpm to obtain a carbon nanotube antistatic silicone rubber material;
[0084] Step 2: Add the carbon nanotube antistatic silicone rubber material into a grinder, grind it 10 times under the condition of a roller pressure of 5 kg, and then cure the coating at room temperature to obtain a carbon nanotube antistatic protective film.
[0085] Comparative Example 5
[0086] A method for preparing a carbon nanotube antistatic protective film comprises the following steps:
[0087] Step 1: CM@CNTs-PDA antistatic agent is prepared by the following steps:
[0088] S1. Same as Example 1;
[0089] S2. The product 1 was placed in a N2 atmosphere with a flow rate of 15 mL / min, heated to 300°C at a heating rate of 3°C / min, calcined for 2 h, and then naturally cooled to room temperature to obtain CNTs-PDA;
[0090] S3. Same as Example 1;
[0091] Step 2, add 2 parts of the above-prepared CM@CNTs-PDA antistatic agent and 1 part of the crosslinking agent to 97 parts of 107 silicone rubber, and stir and mix at a speed of 300 rpm to obtain a carbon nanotube antistatic silicone rubber material;
[0092] Step 3: Add the carbon nanotube antistatic silicone rubber material into a grinder, grind it 10 times under the condition of a roller pressure of 5 kg, and then cure the coating at room temperature to obtain a carbon nanotube antistatic protective film.
[0093] The comprehensive performance test of the carbon nanotube antistatic protective films prepared in Examples 4-6 and Comparative Examples 1-5 was performed:
[0094] Surface resistance test: refer to GB / T 1410-2006;
[0095] Stability test: 23℃±2℃, 60%RH for 672h, test surface resistivity;
[0096] High temperature resistance test: 120℃×2h, after baking in a blast oven, place at 23℃±2℃, 60%RH for 2h, and test the surface resistivity;
[0097] Tensile strength test: refer to GB / T 2567-2021;
[0098] Appearance: Evaluation of appearance of foreign matter such as glue spots and carbon spots;
[0099] The test results are shown in Table 1:
[0100] Table 1
[0101]
[0102] It can be seen from Table 1 that by adding CM@CNTs-PDA antistatic agent to the low viscosity silicone rubber system, using polydopamine as an intermediate medium to perform bidirectional hydroxyl functionalization on carbon nanotubes and nanocellulose, the modified carbon nanotubes are given good dispersibility and flexibility in the silicone rubber system. The prepared antistatic protective film has low resistance and can effectively conduct current, thereby playing an antistatic role, and has good mechanical properties. There are few foreign matters such as glue points and carbon points in the cured protective film layer, and the appearance is excellent, which meets the use requirements.
[0103] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0104] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A carbon nanotube antistatic protective film, It is characterized in that Includes the following mass components: CM@CNTs-PDA antistatic agent 1-3 parts; Silicone rubber 95-98 parts; 1-2 parts of cross-linking agent; The CM@CNTs-PDA antistatic agent is prepared by the following steps: S1. Add dopamine precursor solution to the carbon nanotube suspension, stir and react for 10-24h, collect by centrifugation and vacuum dry to obtain product 1; S2. Place product 1 in N 2 In the atmosphere, the mixture was calcined in a gradient manner and then naturally cooled to room temperature to obtain CNTs-PDA; S3. Add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, hydroxysuccinimide and CNTs-PDA to the nanocellulose solution, mix well, adjust the pH to 4-6, and stir the reaction under vacuum conditions for 8-20 hours. After the reaction is completed, collect by centrifugation and vacuum dry to obtain CM@CNTs-PDA antistatic agent.
2. The carbon nanotube antistatic protective film according to claim 1, It is characterized in that The mass percentage of CNTs and dopamine precursor in S1 is 55-65:35-45wt%.
3. The carbon nanotube antistatic protective film according to claim 1, It is characterized in that The S2N 2 The flow rate is 10-20 mL / min.
4. The carbon nanotube antistatic protective film according to claim 1, It is characterized in that The gradient calcination in S2 is specifically to increase the temperature to 200-250°C at a heating rate of 3-5°C / min, keep the temperature for 0.5-1.5h, then increase the temperature to 320-350°C at a heating rate of 1-2°C / min, and keep the temperature for 0.5-1.5h.
5. The carbon nanotube antistatic protective film according to claim 1, It is characterized in that The mass concentration of the nanocellulose solution in S3 is 0.4-0.8wt%.
6. The carbon nanotube antistatic protective film according to claim 1, It is characterized in that The usage ratio of the nanocellulose solution, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, hydroxysuccinimide and CNTs-PDA in S3 is 100 mL: 0.5-0.6 g: 0.2-0.4 g: 0.6-0.9 g.
7. The carbon nanotube antistatic protective film according to claim 1, It is characterized in that The viscosity of the silicone rubber is 500-1500 mPa·s.
8. A method for preparing the carbon nanotube antistatic protective film as claimed in claim 1, It is characterized in that The following steps are involved: Step 1, adding 1-3 parts of CM@CNTs-PDA antistatic agent and 1-2 parts of crosslinking agent to 95-98 parts of silicone rubber, stirring and mixing to obtain carbon nanotube antistatic silicone rubber material; Step 2: Add the carbon nanotube antistatic silicone rubber material into a grinder, grind it for 9-12 times under the condition of a roller pressure of 4.5-5.5 kg, and then cure the coating at room temperature to obtain a carbon nanotube antistatic protective film.
